Urgensi Pemahaman Masyarakat Sipil tentang Radikalisme di Sumatera Selatan - Sanny Nofrima; Isabella Isabella; Ahmad Baidawi; Herdin Arie Saputra (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
Radicalism is an important element of social movements advocating for individuals or groups seeking ideological emancipation, fostering critical perspectives, and striving for change directly linked to broader adversaries and goals. Vulnerability to radicalism exists at varying intensities, rendering individuals or groups susceptible to radicalization. This research examines a significant issue of potential radicalism identified in previous studies, which appears to surpass society's understanding. The study aims to investigate several dimensions, including understanding, attitudes, and actions with the potential for radicalization. A quantitative method involving face-to-face interview techniques was utilized. The research sample consisted of 400 stratified random samples, which were selected based on characteristics such as gender, marital status, age, occupation, and religion, using the Slovin formula: n = N / (1 + (N x e²)) with a sampling error of 5%, and three hypotheses concerning attitude, understanding, and action. This research also employs a Scopus-based mapping of radicalism, analyzing the network in detail. The findings of the research show that attitude, understanding, and action have a direct impact on radicalism. Additional findings reveal that attitudes exert the greatest influence on the potential for radicalism, followed by understanding and actions. When viewpoints become extreme, inflexible, or intolerant, attitudes can reveal a person's propensity toward a particular ideology or societal issue. By encouraging the avoidance of possible radicalism and supporting improved decision-making in society, healthy social interactions can raise awareness of the hazards of radicalism. The interaction between attitudes, understanding, actions, and the potential for radicalism is a dynamic process that progressively leads to radical involvement within a specific context.